Selected Features of a Unique Persian Manual on Islamic Administration from Late Safavid Iran: Mirza Rafi'a's Dastur Al-Muluk - Marcinkowski, Muhammad Ismail (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2014)
Selected Features of a Unique Persian Manual on Islamic Administration from Late Safavid Iran: Mirza Rafi'a's Dastur Al-Muluk